Data boosting on short bivariate time series data by Sieve Bootstrap - Pantino, Ma. Salvacion B.
Abstract (A model is postulated given a short bivariate time series data with high-dimensional inputs. The correlated response vectors are functions of the contemporaneous effects of the input series. The model is then estimated using a hybrid of methods embedded into the backfitting algorithm. It is noted from the simulation studies that the estimation procedure produces parameter estimates with lower relative bias and better predictive ability compared to VAR(1). The estimation method is also robust to misspecification errors).